'A pedagogy of the image': Chantal Akerman's ethics across film and art. (1st September 2019) - Rennebohm, Kate
This article elucidates the complex ethical paradigm at the heart of Chantal Akerman's work and thought, arguing first that her ethics are as concerned with the figure of the self as they are with the figure of the other and that, second, these ethics exist as much in the spatial and durational structures of her work as in the content of her images. In this way, this article contends that approaching Akerman's work through the question of ethics allows one to see consistencies across her film and installation work, even as her aesthetic strategies shift across the different dispositifs of the cinema and the gallery or museum. Addressing these shifts, I offer the concept of Akerman's 'ethical pedagogy of the image' – a term that implies both a method and a site of instruction. Drawing on these two meanings, this article ultimately reveals that Akerman's pedagogical aim involves turning viewers' ethical attention back on to themselves – to offer a prompt and a space for reconsideration of their own ethos.